Hemodialysis Catheter-Related Blood Stream Infection: Rates, Risk Factors And Pathogens (Journal of Dhaka Medical College, 2023)
Background: Central venous catheters (CVC) are an important means of delivering hemodialysis (HD) to patients who require immediate initiation of dialysis. Haemodialysis (HD) catheter-related bloodstream infections (CRBSIs) are a major complication of long-term catheter use in HD.Aims: This study was conducted to identify the rates, risk factors and spectrum of infecting organisms of Hemodialysis catheter-related blood stream infection (CRBSI).Methods: This prospective Observational study was carried out in the Department of Nephrology, Dhaka Medical College Hospital, Dhaka during January 2018 to July 2019. A total of 125 patients with Central Venous Catheter for Hemodialysis were included in this study.Results: Twenty four patients with a mean age of 42.9±17.5 years were confirmed to have CRBSI with a rate of 6.6 per 1000 catheter days in Temporary Uncuffed Catheter group and 1.4 per 1000 catheter days in Permanent Cuffed Catheter group. Independent risk factor associated with CRBSI was diabetes. 70.8% patients had gram-negative infections, 4(16.7%) patients had gram-positive infections and 3(12.5%) patients had polymicrobial infections. Pseudomonas species (37.5%) were the most common identified bacteria.Conclusion: The rate of CRBSI in Hemodialysis patients was significant and the only identified risk factor was diabetes mellitus. Infection by Gram-negative bacteria was noteworthy among the patients.J Dhaka Med Coll. 2021; 29(1): 3-8